ON LINEAR INFINITE SYSTEMS RELATED TO WAVE SCATTERING PROBLEMS FOR PLANAR WAVEGUIDE JUNCTIONS WITH A RECTANGULAR REGION OF INTERACTION - Chumachenko, Y.V.; Chumachenko, V.P. (Radio Electronics, Computer Science, Control, 2013)
Application of the domain-product technique (DPT) to scalar scattering problems in planar waveguide transformers with rectangular coupling cavities (e.g. right-angle bends, T-junctions, cross-junctions and the like) yields one-type matrix-operator equations for both H- and E-plane configurations. This makes it possible to consider the features of the respective mathematical models through the example of a relatively simple representative, namely, an H-plane bend with a dielectric loaded connecting region.